1980
DOI: 10.1159/000137409
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Blood Flow on Intestinal Absorption of Xenobiotics

Abstract: The dependence of intestinal absorption of xenobiotics on the blood flow rate increases from blood flow independent to blood flow limited absorption as the absorbabilitiy of the substances increases. Since the absorbed substances are mainly drained by the blood flowing through the subepithelial vessels, not only the total flow rate of an intestinal segment but also the intramural blood flow pattern influences the absorption rate. The villous countercurrent exchange represents an additional resistance to the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 48 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…The relative contribution to the total resistance offered by ABL along the blood capillaries is not clear, but impaired blood flow rates have been shown to slow absorption in the dog, 37 cat, 38 and rat. 39 Several factors, including an increase in thickness of the ABL, decreased oxygen supply, and altered metabolic mechanisms may lead to decreased absorption during reduced blood supply. 36,40 However, under normal physiological conditions, the rate of blood flow is believed to be high enough so that only minimal resistance to mass transport is offered by this ABL, 36 so the contribution of 1/P ABL blood to the apparent permeability in eq 4 can be neglected.…”
Section: Methodsmentioning
confidence: 99%
“…The relative contribution to the total resistance offered by ABL along the blood capillaries is not clear, but impaired blood flow rates have been shown to slow absorption in the dog, 37 cat, 38 and rat. 39 Several factors, including an increase in thickness of the ABL, decreased oxygen supply, and altered metabolic mechanisms may lead to decreased absorption during reduced blood supply. 36,40 However, under normal physiological conditions, the rate of blood flow is believed to be high enough so that only minimal resistance to mass transport is offered by this ABL, 36 so the contribution of 1/P ABL blood to the apparent permeability in eq 4 can be neglected.…”
Section: Methodsmentioning
confidence: 99%
“…Several mathematical models have been discussed relating the effect of altered blood flow to drug absorption, taking into account altered permeability [Winne, 1977[Winne, , 1978[Winne, , 1980Kubota and Ishizaki, 19861, distribution [Weiss, 1983;Robinson and Rapoport, 19861, elimination [Rowland et al, 1973;Luecke and Wosilait, 1979;Goodacre and Murray, 1981;Bass, 1983;Huang and Oie, 1984;Rubin and Tozer, 1984;Wellhoner, 1985;Roberts and Rowland, 1986;Chiou, 19871, and general disposition [Chen and Andrade, 19761. Although these models provide many interesting theories of the differential effects of blood flow on the pharmacokinetics of flow vs. capacity-limited drugs, one vs. two-compartmental models, or permeable vs. impermeable drugs, they do not discuss the effect of exercise which may alter the drug pharmacokinetics.…”
Section: Effect Of Exercise On Pharmacokineticsmentioning
confidence: 99%
“…Important in intestinal drug absorption is the removal of drugs from enterocytes by the intestinal venous blood, which is about 75% of total liver blood flow. This blood flow not only contributes to the rate of intestinal absorption [179], but also defines the rate at which the solutes reach the first pass clearance organs, the liver and lung, en route to the systemic circulation. Meier and Sturm have observed that elderly patients have a reduced intestinal functional reserve and present a clinical view that age related impaired blood flow, ischaemic changes and increased NSAID…”
Section: Accepted Manuscriptmentioning
confidence: 99%